Crystal structure of (E)-7-hydroxy-2-((6-methoxypyridin-2-yl)methylene)-3,4-dihydronaphthalen-1(2H)-one, C17H15NO3 - Liang Lun-Hai; Zhao Feng-Lan; Meng Qing-Guo (Zeitschrift für Kristallographie - New Crystal Structures)
C17H15NO3, triclinic, P1‾$P‾{1}$ (no. 2), a = 7.5016(4) Å, b = 13.6750(8) Å, c = 14.8557(9) Å, α = 115.469(6)°, β = 91.726(5)°, γ = 97.325(5)°, V = 1358.48(15) Å3, Z = 4, Rgt(F) = 0.0442, wRref(F2) = 0.1095, T = 100 K.